Volume electron microscopy: analyzing the lung. - Schneider, Jan Philipp; Hegermann, Jan; Wrede, Christoph (Histochemistry & Cell Biology, 2021)
Since its entry into biomedical research in the first half of the twentieth century, electron microscopy has been a valuable tool for lung researchers to explore the lung's delicate ultrastructure. Among others, it proved the existence of a continuous alveolar epithelium and demonstrated the surfactant lining layer. With the establishment of serial sectioning transmission electron microscopy, as the first "volume electron microscopic" technique, electron microscopy entered the third dimension and investigations of the lung's three-dimensional ultrastructure became possible. Over the years, further techniques, ranging from electron tomography over serial block-face and focused ion beam scanning electron microscopy to array tomography became available. All techniques cover different volumes and resolutions, and, thus, different scientific questions. This review gives an overview of these techniques and their application in lung research, focusing on their fields of application and practical implementation. Furthermore, an introduction is given how the output raw data are processed and the final three-dimensional models can be generated.